Stubborn boundaries: the iron ring ritual as a case of mapping, resisting, and transforming Canadian engineering ethics - Paul, Robyn Mae; Zacharias, Kari; Nolan, Edmund Martin; Monkman, Kyle; Thomsen, Victoria (Frontiers in Education, 2023)
This article discusses the historical context and ongoing discussions of the iron ring ritual, a prominent tradition in Canadian engineering. We employ discourse analysis to describe and analyze components of the ritual itself, as well as more recent texts related to contemporary conversations about the ritual. We apply Alice Pawley’s scholarship on boundary work in engineering as an analytical framework and find the ritual has served to reproduce and map boundaries around engineering ethics and responsibility in Canada, and numerous actors have resisted those boundaries based on opposition to the colonial, misogynistic, and Christian values embedded in the ritual, as well as the ritual’s framing of engineering agency and responsibility. We reflect on the lessons this case can offer for members of the Canadian engineering and engineering education communities, as well as for those interested in the power and complexity of humanistic interventions in engineering.